Paciente de sexo masculino de 65 años de edad con accidente cerebro vascular e hipertensión arterial. - Terán Hidalgo, Angie Maylin (2018)
High or High blood pressure is also known as arterial hypertension, is a disorder in which the blood vessels have a persistently High tensión, which can damage them, is the force exerted by the blood against the walls of the vessels (arteries) to the be pumped by the heart. The higher the tensión, the more effort the heart has to make to pump. When performing a comprehensive nutritional assessment it is concluded that the patient according to the anthropometric data is in a normal state, according to the biochemical values present hypernatremia which was controlled. In reference to the clinical values blood pressure that was High decreased to 130/70 mmHg, the redness of the face decreased markedly A feeding plan was made according to the pathology under study, this being a diet using a nasogastric tube plus a nutritional formula of 133.08 kcal distributed over 5 meal times in order to maintain nutritional status The follow-up given to this case through the control of anthropometric, biochemical and clinical data allowed the patient to maintain their nutritional status, the diet prescribed by nasogastric tube lasted 3 weeks after this, food tolerance was initiated.